Pengelolaan Pembibitan Tanaman Kehutanan dalam Mendukung Kegiatan Rehabilitasi Lahan: Forestry Plant Nursery Management in Support of Land Rehabilitation Activities - Zulkaidhah, Zulkaidhah; Wahyuni, Dewi; Hapid, Abdul; Rahmawati, Rahmawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Quality seedlings are characterized by their ability to adapt to their environment, grow well when planted, and are healthy and uniform. The quality of seedlings will determine the quality of future plants that play a role in land rehabilitation activities. Land rehabilitation activities preferably involve farmer groups from the local community, especially those around the location of the activity. The involvement of the surrounding community can increase community participation in plant maintenance. The purpose of the service is to help village communities living around the Production Forest area of KPH Sivia Patuju through increased knowledge of Nursery Management. Extension activities are carried out using the method of delivering material to individuals, groups, and masses while training through lectures, discussions, and tutorials. The results of the service consisted of counseling activities in the form of material on seed scarification and the use of good planting media. Training activities consist of how to make solid and liquid organic fertilizers. The community service activities provided good results in nursery management characterized by maximum seedling growth. The success of the nursery is evidence of an increased understanding of the community.